Comparative Analysis of Moora and Waspas Methods for Selecting the Best Supplier - Sartika Lina Mulani Sitio (LPPM Politeknik Aceh Selatan, 2025)
Selecting the right supplier is an important element in the K-24 Pharmacy supply chain, as it directly impacts the availability and quality of drugs provided to customers. However, the supplier selection process is often faced with the complexity of various criteria that must be considered simultaneously. This creates problems in decision making that are often subjective and less than optimal. To overcome this problem, this study proposes a solution in the form of implementing the MOORA (Multi-Objective Optimization by Ratio Analysis) and WASPAS (Weighted Aggregated Sum Product Assessment) methods to support the best supplier selection process at K-24 Pharmacy. The purpose of this study is to develop a system that can provide objective and measurable supplier recommendations, based on various relevant criteria. This study uses data from several potential suppliers considered by K-24 Pharmacy. Relevant criteria are weighted based on their level of importance through interviews with pharmacy management. The criteria used in this research are delivery speed, discounts, service, warranty, authenticity of goods, payment terms and return of goods. Furthermore, the MOORA method is used to conduct multi-objective ratio analysis, while the WASPAS method combines the weighted sum and weighted product approaches to evaluate the overall performance of each supplier. The results of the study indicate that both methods are effective in providing consistent recommendations for selecting the best supplier. However, the WASPAS method is superior in providing more accurate and comprehensive results because of its ability to combine various aspects of evaluation. The implementation of the MOORA and WASPAS methods is expected to help the management of Apotek K-24 in making more appropriate decisions and reducing the risks associated with supplier selection.